Community Empowerment School Closure Localization Dolly in Kelurahan Putat Jaya Sawahan Surabaya - Wiwik Handayani; Sri Mulyaningsih; Wiludjeng Widayati (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2017)
The closure of the localization of Dolly has issues of its own for the surrounding community or communities affected. This is due to the lack of the skills possessed by the localization community around, causing the decline in family income. Through the activities of the service are expected to improve the skills of the community affected and its revenues. Activities include training in entrepreneurship, dedication to the creation of creative effort, packaging, processing of catfish into a dumpling, nugget and mince. The selection of catfish as a base material because the Catfish is easy to get, cheap and easily cultivated by rural communities as well as urban areas. In addition to the fish is a very good protein for growing children and also adults because of low colesterol. Training activities are conducted four times by way of direct practice so that they really can do it yourself after you finish training. In an effort to increase revenue, after completion of the training the participants were required to produce and sell it as well as do mentoring. Thus the process of evaluation and monitoring will help affected communities business growth.